Peran Kepala Desa Sebagai Motivator Untuk Meningkatkan Kreativitas Pembangunan Ekonomi Desa Kloangpopot Kecamatan Doreng Kabupaten Sikka - Fransiskus Risaul; Muhamad Taufik Arifin; Muhamad Syahrun (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
The purpose of this study was to find out the role of the village head in increasing the creativity of the economic development of the people of Kloangpopot village, Doreng sub-district. the people of Kloangpopot Village, Doreng District, Sikka Regency. Jenins research uses qualitative research, and data collection techniques, namely interviews, observation, and documentation. The results showed that the role of the village head in increasing the creativity of the economic development of the Kloangpopot village community, Doreng subdistrict, Sikka district, had been carried out. This can be seen from community participation in the implementation of Kloangpopot village economic development going well according to 3 indicators, namely through motivator indicators that encourage or motivate the community to involved in implementing economic development in the village such as carrying out the programs that have been given, the indicator of the facilitator is that the village head as a facilitator always provides supporting facilities such as meeting places. such as the village hall facilitated by the village head to discuss economic development in the village kloangpopot, the mobilizing indicator moves or invites the community to participate in taking concrete actions to develop the village, for example mobilizing the community in village meetings. While the obstacle to the role of the village head in increasing the creativity of the economic development of the people of Kloangpopot village, Doreng sub-district, Sikka district, is the lack of availability of human and community resources that are not yet professional in building creative villages.